2012
DOI: 10.1080/1745039x.2012.663668
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sodium butyrate and salinomycin upon intestinal microbiota, mucosal morphology and performance of broiler chickens

Abstract: The effect of dietary sodium butyrate (SB) or salinomycin (SAL) or both additives on performance, small intestinal morphology and microbial ecology of broiler chickens was studied. A growth trial was conducted with 96 Ross 308 female broilers from 1 to 30 days of age. Four treatment groups were fed with a non-supplemented control diet or three experimental diets supplemented with i) 300 mg SB (Adimix 30 coated) per kg, ii) 60 mg SAL (Sacox) per kg or iii) both additives in combination. Feed intake and body-wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
38
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 30 publications
9
38
3
Order By: Relevance
“…These results are in agreement with Smulikowska et al (2009), Zhang et al (2011) and Czerwiński et al (2012. Collectively, these studies suggested that the dietary addition of SB did not have significant effects on WG, FI and FCR of birds grown in hygienic conditions and with high health status (Smulikowska et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results are in agreement with Smulikowska et al (2009), Zhang et al (2011) and Czerwiński et al (2012. Collectively, these studies suggested that the dietary addition of SB did not have significant effects on WG, FI and FCR of birds grown in hygienic conditions and with high health status (Smulikowska et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, in the current study, SB did not affect ileal and caecal pH values and SCFA contents. Similar findings were reported in literature (Mahdavi and Torki, 2009;Smulikowska et al, 2009;Czerwiński et al, 2012). However, the current study showed that SB at a higher dose (2 g/kg) significantly increased growth rate for the birds fed wheat-based diets.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The body weight gain obtained in this study with respect to higher level organic acid inclusion agreed with the result of Oruwari et al, (1993) who observed calcium propionate increased the body weight at the dose rate of 1 g/kg and also agreed with Khosravi et al, (2008) who had incorporated the calcium propionate at the dose rate of 2 g/kg. Likewise, in coated sodium butyrate supplemented treatment, results were in agreement with Hu and Guo (2007), Czerwinski et al, 2012, Brozoska et al, (2013 reiterated that sodium butyrate added to the diets broiler enhanced the body weight gain. The organic acid incorporated in the diet might have a positive influence on the digestibility of in-fed nutrients, improves the gut health and that could be the reason for higher body weight gain in the groups supplemented with OAs and the same can be confirmed with the dose dependant improvement noticed in the body weight gain in those groups.…”
Section: Body Weight and Weight Gainsupporting
confidence: 79%
“…The results confirmed that microbiota modulation through ionophore coccidiostats is based on the suppression of Gram-positive pathogens such as Clostridium perfringens (Bjerrum et al, 2005), which causes necrotic enteritis in poultry, and by limiting proliferation of Bacteroides, Clostridiacae, Enterobacteriacae and Lactobacillus spp./Enterococcus spp. which can compete with the host-bird for nutrients uptake as well as impair fat absorption through bile acid deconjugation (Masuda, 1981;Klaver and van der Meer, 1993;Czerwiński et al, 2012).…”
Section: Discussionmentioning
confidence: 99%